KONTRIBUSI CULTURE SHOCK TERHADAP SELF ADJUSTMENT MAHASISWA KELAS INTERNASIONAL UNIVERSITAS NEGERI PADANG - Puji Gusri Handayani; Verlanda Yuca (Universitas Negeri Padang, 2019)
This study aims to describe culture shock and self adjustment on students, and examine the contribution of culture shock to student self adjustment. The population is the international class students of Padang State University as many as 212 students using simple random sampling techniques. The research method uses descriptive and regression. The instruments used were